2018
DOI: 10.1111/1365-2664.13297
|View full text |Cite
|
Sign up to set email alerts
|

Flow–ecology relationships are spatially structured and differ among flow regimes

Abstract: 1. In streams, hydrology is a predominant driver of ecological structure and function.Providing adequate flows to support aquatic life, or environmental flows, is therefore a top management priority in stream systems.2. Flow regime classification is a widely accepted approach for establishing environmental flow guidelines. However, it is surprisingly difficult to quantify relationships between hydrology and ecology (flow-ecology relationships) while describing how these relationships vary across classified flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 61 publications
5
34
0
Order By: Relevance
“…Various studies have emphasised the importance of widely applicable flow-ecology relationships to underpin studies of riverine ecosystems (including regulated systems) at larger spatial scales (Webb et al, 2013;Bruckerhoff, Leasure & Magoulick, 2019). The current study demonstrated consistent responses of benthic diatom assemblages to water supply reservoirs in England, but also highlighted that the predictive power at the largest spatial scales was comparatively low.…”
Section: Study Implicationsmentioning
confidence: 50%
“…Various studies have emphasised the importance of widely applicable flow-ecology relationships to underpin studies of riverine ecosystems (including regulated systems) at larger spatial scales (Webb et al, 2013;Bruckerhoff, Leasure & Magoulick, 2019). The current study demonstrated consistent responses of benthic diatom assemblages to water supply reservoirs in England, but also highlighted that the predictive power at the largest spatial scales was comparatively low.…”
Section: Study Implicationsmentioning
confidence: 50%
“…Various studies have emphasised the importance of widely applicable flow-ecology relationships to underpin studies of riverine ecosystems (including regulated systems) at larger spatial scales (Webb et al, 2013;Bruckerhoff et al, 2019). The current study demonstrated consistent responses of benthic diatom assemblages to water supply reservoirs in England, but also highlighted that the predictive power at the largest spatial scales was comparatively low.…”
Section: Study Implicationssupporting
confidence: 47%
“…Because we were interested in using generalised linear mixed effect models as a variable reduction tool and were not interested in interactive effects, we only developed global, additive effect models for each response variable. To account for spatial autocorrelation in fish community structure responses to abiotic factors (Bruckerhoff et al., 2019), we included HUC level 10 catchment nested within major drainage basin as a random effect to control for spatial clumping of sites within catchments. Year was also included as a main effect in all models.…”
Section: Methodsmentioning
confidence: 99%